Production of transgenic sheep: Microinjection of the bovine P77 gene construct in Chios sheep breed zygotes - VAINAS (Ε. ΒΑΪΝΑΣ), E.; BESENFELDER, U.; CHRISTODOULOU (B. ΧΡΙΣΤΟΔΟΥΛΟΥ), V.; KUEHHOLZER, B.; AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), G. C.; BELIBASAKI (Σ. ΜΠΕΛΙΜΠΑΣΑΚΗ), S.; BREM, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The feasibility of integration of the bovine P77 construct into zygotes and two cell embryos of Chios sheep breed was examined. The P77 gene construct comprised bovine as l casein promoter regulatory sequence fused to the fragment between exons 2 and 9 of the bovine chymosin gene. One of the two pronuclei of the zygote or a nucleus of a blastomere of a two cell embryo was microinjected with 1 pi of DNA solution containing approximately 1000 copies of the gene construct. In total 193 zygotes and 87 two cell embryos collected from 49 donor ewes were used. After 1 - 5 h culture microinjected zygotes (n=175) and two cell embryos (n=76) were transferred by a laparoscopic technique to the oviducts of 68 recipients. 22 recipients (32.4%) gave birth to 29 lambs which correspond to 11.6% of the total number of zygotes - embryos transferred. PCR analysis performed in skin samples of these lambs revealed that in one ewe lamb the P77 construct has been integrated in its genome. The growth and puberty of this lamb was physiological and is currently pregnant. This is the first transgenic farm animal born in Greece.